Systematic review and meta-synthesis of coping with retinitis pigmentosa: implications for improving quality of life - Gulcan Garip; Atiya Kamal (BMC Ophthalmology, 2019)
Abstract Background Retinitis pigmentosa (RP) are a group of incurable and inherited eye conditions, and the leading cause of inherited blindness in people under the age of 60. The aim of this systematic review and meta-synthesis was to present a comprehensive overview of qualitative papers on experiences and coping strategies of adults living with RP, and how these influence quality of life. Methods A pre-registered search strategy was applied in nine databases and 12 articles met eligibility criteria. Studies included were from Australia, Brazil, Ireland, Netherlands, Republic of Korea, United Kingdom, and USA. The overall sample was based on 126 people with RP (ages ranging from 18 to 85; at least 65 female). Principles of meta-ethnography were used to synthesise the articles revealing five higher-level meta-themes. Results The five higher-level meta-themes were, 1) managing identity: making sense of RP, managing autonomy and independence; 2) living with RP: practical and emotional issues; 3) experiences with healthcare professionals and other social support; 4) adaptive and maladaptive coping strategies; and 5) impact of RP on work and career. A conceptual model was developed by grouping higher-level meta-themes as intra- and inter-individual factors and how they may be implicated with coping strategies and quality of life. Conclusions This review established factors that can be explored as potential psychosocial influences in the relationship between coping strategies and quality of life in people with RP. Further understanding of these factors and mechanisms can help inform intervention development to support adaptive coping in living with RP and positively impact quality of life.